1996
DOI: 10.1002/pen.10412
|View full text |Cite
|
Sign up to set email alerts
|

Elastomer‐toughened poly(phenylene sulfide)

Abstract: For use as electrical and electronics parts, or automobile and mechanical parts, toughened poly(pheny1ene sulfide) (PPS) is desired. For these applications, our investigation centered on improving the toughness of PPS and developing elastomer-toughened PPS and elastomer-toughened compounds of PPS. Using chemically treated PPS and an olefinic elastomer with a functional group, we developed elastomer-toughened PPS using a reactive processing method. In the PPS matrix, the elastomer is finely dispersed. While the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 3 publications
(1 reference statement)
1
28
0
Order By: Relevance
“…It was also attempted to blend reactive ethylene copolymer containing about 2 wt% of maleic anhydride and PPS chemically treated with diphenylmethane diisocyanate in an extruder before the melt blending. 27 Scanning electron microscopy measurements showed that the resultant blend composed of (80/20) so-modified PPS and the 0 100 78 14 839 NB 80 20 0 0 802 36 221 300 80 0 20 0 698 44 45 141 80 0 0 20 868 41 9 -90 10 0 0 945 43 188 204 80 20 0 0 802 36 221 300 70 30 0 0 220 13 13 165 90 0 10 0 757 58 22 77 80 0 20 0 698 44 45 141 70 0 30 0 548 44 312 441 Abbreviations: EB, elongation at break; EMA-GMA, poly(ethylene-ran-methylacrylate-ranglycidyl methacrylate); EGMA-g-PMMA, poly(ethylene-ran-glycidyl methacrylate)-graftpoly(methyl methacrylate); IS, tensile impact strength; LDPE, linear low-density polyethylene; NB, non-breakable; TM, tensile modulus; TS, tensile strength. ethylene copolymer had an average domain size of 0.25 mm, whereas the blend prepared using unmodified (conventional) PPS had an average domain size of 1 mm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also attempted to blend reactive ethylene copolymer containing about 2 wt% of maleic anhydride and PPS chemically treated with diphenylmethane diisocyanate in an extruder before the melt blending. 27 Scanning electron microscopy measurements showed that the resultant blend composed of (80/20) so-modified PPS and the 0 100 78 14 839 NB 80 20 0 0 802 36 221 300 80 0 20 0 698 44 45 141 80 0 0 20 868 41 9 -90 10 0 0 945 43 188 204 80 20 0 0 802 36 221 300 70 30 0 0 220 13 13 165 90 0 10 0 757 58 22 77 80 0 20 0 698 44 45 141 70 0 30 0 548 44 312 441 Abbreviations: EB, elongation at break; EMA-GMA, poly(ethylene-ran-methylacrylate-ranglycidyl methacrylate); EGMA-g-PMMA, poly(ethylene-ran-glycidyl methacrylate)-graftpoly(methyl methacrylate); IS, tensile impact strength; LDPE, linear low-density polyethylene; NB, non-breakable; TM, tensile modulus; TS, tensile strength. ethylene copolymer had an average domain size of 0.25 mm, whereas the blend prepared using unmodified (conventional) PPS had an average domain size of 1 mm.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Studies in this group are very limited compared with the other two groups, because it is believed that the general-purpose polymers cannot tolerate the high temperature process required for blending with PPS. Chen et al 24 studied blends composed of PPS and polyethylene at various component ratios and described the relationship between the domain size and the composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our former study for the toughened PPS from the PPS/elastomer alloy system suggested that, to obtain the toughened PPS, the elastomer particle should be below 0.4 lm. [6] Considering this fact, a more finely dispersed PPE in the PPS matrix may be desired.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, new methods for the preparation of elastomer-toughened PPS were developed. In this method, PPS was chemically treated with diphenylmethane diidocyanate to activate the reactivity of the PPS end-group [5].…”
Section: Introductionmentioning
confidence: 99%